Intrauterine nutrition and carotid intimal media thickness in young Thai adults. - Rerkasem K. (2014)
Several studies show that intrauterine nutrition restriction is associated with vascular disease. Animal studies have shown that atherosclerosis can be affected by a constrained intrauterine diet, but this relationship in humans is controversial. The purpose of this study was to investigate the relationship between maternal intake during pregnancy and carotid intimal media thickness (CIMT). We measured CIMT in 565 twenty year old young adults whose mothers, while pregnant, participated in a nutritional study during 1989-1990 at two hospitals in Chiang Mai, Thailand. Maternal diet during pregnancy was assessed by two methods in each trimester, namely, the 24 hours food recall method and the food frequency method. Carotid intimal media thickness was greater in males and participants who showed higher blood glucose, higher body mass index and higher systolic blood pressure. Maternal protein intake during the first trimester was negative correlated with thickness of CIMT (p=0.02). The mean CIMT of participants whose mothers were in the lowest quarter of the distribution of protein intake in the first trimester was 0.45 mm (95% confidence interval (CI): 0.44-0.46) more than that of those whose mothers were in the highest quarter of the distribution (0.43 mm 95% CI: 0.42-0.44). In conclusion, lower maternal protein intake during early pregnancy may increase CIMT in adolescents.